The High-Intensity Exercise Study to Attenuate Limitations and Train Habits in Older Adults With HIV (HEALTH): A Research Protocol. (25th March 2022) - Oliveira, Vitor H. F.; Erlandson, Kristine M.; Cook, Paul F.; Jankowski, Catherine; MaWhinney, Samantha; Dirajlal-Fargo, Sahera; Knaub, Leslie; Hsiao, Chao-Pin; Horvat Davey, Christine; Webel, Allison R.
Abstract: The High-Intensity Exercise Study to Attenuate Limitations and Train Habits in Older Adults With HIV (HEALTH), which incorporates an exercise and biobehavioral coaching intervention, has the following overall goals: (a) to determine whether high-intensity interval training (HIIT) mitigates physical function impairments, fatigue, and impairments in mitochondrial bioenergetics of older people living with HIV (PLWH) to a greater extent than continuous moderate exercise (CME); and (b) to determine whether a biobehavioral coaching and mobile health text messaging intervention after HIIT or CME can promote long-term adherence to physical activity. The HEALTH study is a randomized trial of 100 older PLWH (≥50 years of age) who self-report fatigue and have a sedentary lifestyle. Enrolled participants will be randomized to 16 weeks of supervised HIIT or CME training, followed by a 12-week maintenance phase, involving a mobile health coaching intervention. Outcomes of the HEALTH study will inform the development of scalable, effective exercise recommendations tailored to the unique needs of aging PLWH.